Evaluasi Kualitas Informasi Situs Web Pemerintahan Kota Jakarta Selatan - Amaya, Devina; Prima, Yunita; Priyatna, Centurion Chandratama (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The rapid growth of science and technology has transformed the way humans access information. In the modern era, the internet has become one of the primary mediums for exchanging information among society, with websites being one of its products. The South Jakarta Administrative City Government utilizes its official website (https://selatan.jakarta.go.id/) to disseminate information to the public, in line with the E-Government policy introduced during the administration of Megawati Soekarnoputri. This research aims to evaluate the quality of information presented on the website. Through this study, the problem statement is "What is the quality of information on the South Jakarta City Government website?" This research employs a descriptive method to understand the effectiveness and shortcomings of the web-based information services provided by the government institution.